BUILDING ENERGY SYSTEMS OPERATION OPTIMIZATION WITH ICE STORAGE – A REAL TIME APPROACH - Soltan, Babak Khalifeh; Thorman, Ben (MATTER: International Journal of Science and Technology, 2017)
Energy consumption in BESIS is in close relationship with the operation logic of the associated HVAC. Furthermore, engineering calculation norms describe design conditions as the best operating mode for ISAC. Since the performance of ISAC sub-systems are susceptible to environmental variations and operation priorities, controller based dynamic operation optimization of ISAC sub-systems is desirable from both sustainability and business perspectives. This results in an increment in the corresponding heat transfer rate and ultimately, an improvement in the overall efficiency of the BESIS. In this article the assessment results of the dynamic behavior of BESIS in a typical building under certain optimization strategies is presented. Then BEMWIS has been fitted to BESIS to analyze daily operational data of the energy system, to balance load via stored ice latent heat, and to properly respond to the variable inputs. The knowledge based control system uses equipment operation data and energy consumption, developed in form of data bases and mathematical models. The optimization methodology has been developed based of empirical information from the running ISAC. The optimizer methodology predicts load as the result of the decision maker system calculations, and then records, shifts, and eliminates unnecessary energy consumption.